Drosophila melanogaster inhabiting northern regions of European Russia are infected with Wolbachia which adversely affects their life span - N. V. Roshina; A. V. Symonenko; A. V. Krementsova; Е. A. Tsybul’ko; V. E. Alatortsev; E. G. Pasyukova; D. V. Mukha (Вавиловский журнал генетики и селекции)
Wolbachia is a genus of bacteria causing intracellular infection in the natural populations of Drosophila melanogaster on all continents. In D. melanogaster, Wolbachia affects various life history traits, behaviour, sensitivity to stress and viral infection. The phenotypic effects of Wolbachia might evolve to promote its further spreading, increasing the interest in exploring the spread of Wolbachia, in particular, at the boundaries of the D. melanogaster habitat, in association with the effects on vital traits of host species. In this paper, we present data on the level of Wolbachia infection in two D. melanogaster populations from the northern regions of European Russia: Alexandrov (56.41° N, 38.72° E) and Valday (58.02° N, 33.24° E). The flies were collected in private apple gardens located in two small hamlets without supermarkets or fruit markets, from 2010 to 2015. The both populations demonstrated the same level of infection: in average, 69.7 % of the inbred lines (ILs) obtained from single females of the Alexandrov population and 68.4 % of ILs obtained from single females of the Valday population. The infection rate varied from year to year showing a tendency to reduction, its overall level being within the range previously observed in other habitats. Life spans were compared in sub-lines of the same IL, one infected with Wolbachia and the other treated with tetracycline healing this infection. In four out of five ILs, the lifespan of both males and females was severely affected by Wolbachia; in different ILs, the mean life spans reduced from 1.8 to 5.4 times and from 1.4 to 2.4 times, respectively. Our results confirm that, despite D. melanogaster widespread distribution, the Wolbachia effect on their life span has been mostly negative.